2016
DOI: 10.5312/wjo.v7.i9.519
|View full text |Cite
|
Sign up to set email alerts
|

Return to sports after shoulder arthroplasty

Abstract: Many patients prioritize the ability to return to sports following shoulder replacement surgeries, including total shoulder arthroplasty (TSA), reverse total shoulder arthroplasty (RTSA), and hemiarthroplasty (HA). While activity levels after hip and knee replacements have been well-established in the literature, studies on this topic in the field of shoulder arthroplasty are relatively limited. A review of the literature regarding athletic activity after shoulder arthroplasty was performed using the PubMed da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…They found that both the hemiarthroplasty and RTSA cohorts were able to return to recreational sporting activities, but the RTSA groups significantly outperformed the hemiarthroplasty group in patient-oriented pain outcomes and rates of return to sport. 10 In a comparison of return to sport following TSA, RTSA, and hemiarthroplasty, Johnson et al 8 found that the TSA group (75%-100%) returned to sports at a higher rate than the RTSA (75%-85%) and hemiarthroplasty (67%-76%) groups. Similar rates of return to sport following shoulder arthroplasty and conclusions were found by a separate systematic review and meta-analysis performed by Liu et al 11 …”
Section: Discussionmentioning
confidence: 99%
“…They found that both the hemiarthroplasty and RTSA cohorts were able to return to recreational sporting activities, but the RTSA groups significantly outperformed the hemiarthroplasty group in patient-oriented pain outcomes and rates of return to sport. 10 In a comparison of return to sport following TSA, RTSA, and hemiarthroplasty, Johnson et al 8 found that the TSA group (75%-100%) returned to sports at a higher rate than the RTSA (75%-85%) and hemiarthroplasty (67%-76%) groups. Similar rates of return to sport following shoulder arthroplasty and conclusions were found by a separate systematic review and meta-analysis performed by Liu et al 11 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, avoiding stem-related complications, improved options to gain an anatomic reconstruction of the proximal humerus and preserving the bone stock for easier revisions are practical reasons why stemless designs have been introduced as an alternative to traditional designs. However, both patients and surgeons have high expectations regarding activity levels and return to sports following shoulder replacement surgery[ 8 ]. In regard to these data, the ongoing development of shoulder arthroplasty is a logical consequence.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from the results that RTSA is the best choice for the replacement of the shoulder joint. RTSA implantation and a properly chosen rehabilitation protocol guarantee a high return to non-contact sport and leisure activities at 75% -85% of patients [23][24][25] . The most discussed issue among the authors is the period of fixation of the operated shoulder joint.…”
Section: Resultsmentioning
confidence: 99%